Places as sites of experience - Allen, Sonja, author; Faris, Suzanne, advisor; Osborne, Erika, committee member; Moore, Emily, committee member; Cooperman, Matthew, committee member (Colorado State University. Libraries, 2018)
I am sensitive to my environment, and to how perceptions of an experience within a particular geographic location are effected through the relationship of body, object, and place. My work oscillates between human induced and natural systems, and continues to reveal questions regarding the complex relationship between Americans' and the land in the 21st century. Through the process of mining and manipulating large quantities of earth I reference the land as a resource, while acquainting myself to the specific features that set this landscape apart from the rest of North America. The focus on the landscape translates into my art practice, where I explore how a person's sense of self-identity might become altered through experiences within different places and in light of changing landscapes.
Keywords: sculpture; systems; site specific; rammed earth